Propriedades físico-mecânicas, elétricas e dielétricas de compósitos mulita - fase vítrea - Andrade, Rivaildo Miranda de (2019)
Mullite-glass composites were obtained by solid-state reactive sintering of kaolinite clay and kaolin waste mixtures with waste additions up to 100 wt.%. Rectangular bars were shaped by uniaxial pressing at 40 MPa and fired at 1300 and 1400°C. Mineralogical characterization of raw materials and fired samples was performed by X-ray diﬀractometry (XRD). Physico mechanical properties were inspected using Archimedes’ principle and three-point bending test, respectively. Electrical, dielectric and microestrutural properties of waste free sample and composites (30, 50, 70 and 100 wt.% waste) were assessed by impedance spectroscopy (IS) and field-emission scanning electron microscopy (FESEM), respectively. A dense mullite-glass composite was obtained from 30 wt. % waste addition and sintered at 1400°C. A viscous flux resulting from the glassy fills up the open porosity and increase the mechanical strength. Electrical conductivity, dielectric constant and dielectric loss are strongly dependent on the microstructural features, namely glassy phase and porosity. The activation energy (0.89 - 0.99 eV) for electrical conduction is lower than typical literature values of mullite-based materials. The results give evidences that the herein synthesized mullite-glass composites with up to 53.6 wt.% mullite are promising low-cost materials for electronics-related applications.